The Effect of Spiritual Care on Anxiety Level in Fracture Patients - Budiana Yazid; Rina Rahmadani Sidabutar (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Fractures are the most common physical injuries caused by accidents. The results Riskesdes (2018) show that in Indonesia, there are cases of fractures caused by traffic accidents, falls and sharp or blunt object trauma. Of the 45,987 falls that resulted in fractures, 1,775 people (3.8%) experienced fractures, of the 20,829 traffic accident cases that resulted in fractures. In every province in Indonesia, the most common fracture surgery in the extremities is in Bali with 3,065 cases, DKI Jakarta with 2,781 cases, while in North Sumatra there are 2,576 cases (Mongan & Solikhah, 2023). This study aims to see the effect of spiritual care on anxiety level in fracture patients at Sundari Hospital. This type of research is quasi-experimental with a pre test and post test design with control group. This research was carried out at Sundari Hospital from 11 April to 20 Mei 2025. The study population included 37 patients of fractures. The sampling technique is non-probability sampling. The number of samples in this study was 15 people for the control group and 15 people for the treatment group. The results of the study showed that there was a difference in the average anxiety level of fracture patients who were given spiritual care intervention compared to the group of patients who were not given intervention with p value = 0.000; 95% CI < alpha = 0.05 Keywords: Spiritual care, Anxiety level, Fracture